Philosophy why it matters - Beebee, Helen 1968-; Rush, Michael (Polity, 2019)
"Philosophy is a set of tools and techniques for clearly and systematically considering our arguments and uncovering our hidden assumptions, which helps us to make more informed choices about what to believe and how to act. Philosophy is everywhere, and open to everyone"--
Keywords: Philosophie; Philosophy